Fire Safety Design of a Five Storey Office Building: Fire Design and Smoke Control - Na’inna, A. M.; Lawal, M.S.; Bature, A.S. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Over 75 % of fatalities recorded from fire incidents are attributed to the effects of smoke rather than the direct burning from the fire. A fire safety design and smoke control were conducted in Asha Office Building. A restaurant is considered to be the worst-case scenario. Hence, appropriate fire protection measures such as smoke detectors, heat detectors and sprinklers are to be installed. Using a fire load density of 570 MJ/m2 for an office building, an ignition will take place at 388 seconds. The heat release required at the growth stage of the fire is 1,460 kW and the time required for the smoke detector to respond is 353 seconds. A heat release rate of 10.7 MW at a temperature of 596oC at 956 seconds would be reached before a flashover occurs. At a fully developed fire stage, the heat release rate is almost twice (20 MW) that of flashover stage which is 10.7 MW. The type of smoke control system to be adopted in Asha office building is smoke and heat exhaust ventilation system (SHEVS). For an effective operation of SHEVS at any time, both natural and mechanical ventilators should be installed but not to operate simultaneously in the same smoke reservoir. With a convective heat flux of 5,993 kW, the mass flow rate of smoke in the restaurant is 32 kg/s. A minimum number of three exhaust points will be required based on a volumetric flow rate of 43 m3/s.